Analisis Perbandingan Pendekatan Pengelolaan Lahan untuk Pembangunan Publik di Tanah Adat: Penekanan Bank Tanah Koperasi (BTK) dalam Studi Kasus Minangkabau - Mahargita, Refina; Perdana, Ahmad Baikuni; Syaifullah, Muhammad Yusuf (Jurnal Penelitian Hukum De Jure, 2024)
Customary land, known as tanah ulayat in Indonesia, holds a unique status that differentiates it from other land types, particularly when used for public purposes. Government land acquisition practices risk eroding this status, potentially affecting Indigenous social groups. Cooperation between the government and indigenous communities, through regional governments and other institutions, is recommended as an alternative approach to land acquisition. This research examines various land management tools, focusing on customary land in Minangkabau for public and development purposes. Using a juridical-normative method linked to legal products and content analysis of previous studies, the research identifies three key variables related to customary land: control, utilization, and legality. These variables are analyzed within the context of public interest and research limitations. Three land provision schemes are explored: Land Provision, Cooperative Land Banking (CLB), and Land Commercialization. Each scheme has distinct impacts on land ownership, legality, and the collective well-being of indigenous communities. While Land Provision offers immediate compensation but forfeits land control, CLB and Land Commercialization allow indigenous groups to retain land ownership, with CLB being the preferred option due to its promotion of sustainable land use and active community involvement. The study concludes that CLB is the most viable approach for ensuring long-term economic benefits and land control for Indigenous communities. However, it requires government support regarding legal adjustments and frameworks for cooperation.